ANALISIS KINERJA KESELAMATAN KERJA PARA PERUSAHAAN KONTRAKTOR PADA PERUSAHAAN MIGAS X CILACAP - Clara Dewinda; Yuliani Setyaningsih; Hanifa Maher Denny (STIKes Hang Tuah Pekanbaru, 2019)
Abstract Background : Safety in a company is the main and first thing. No exception in oil and gas company X in Cilacap, Indonesia. This company requires that all contractor companies that send their workers be required to fulfill the Contractor Safety Management System (CSMS) in this oil and gas company. This study is intended to analyze the work safety performance of workers sent by the contractor companies of the oil and gas company X. Methods :This research is a quantitative descriptive study that uses a sample of respondents. The research method used in this study is the survey method by interviewing each selected respondent. Results : The results of this study indicate the relationship between each selected variable related to work safety performance in this oil and gas company X. Conclusion : It is expected that with this research, work safety in oil and gas companies X can be further enhanced for the good in the future. Keywords :work safety performance, contractor companies, oil and gas company